Pengaruh Kompensasi Dan Lingkungan Kerja Fisik Terhadap Semangat Kerja - Rexssa Fitriana; Barin Barlian; Titin Patimah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to determine the effect simultaneously or partially of the variables of Compensation and Physical Work Environment on Work Morale as measured by the population used in this study were 30 Employees of the Manpower Office. The method used in this research is descriptive research with a quantitative approach. Sample selection using saturated samples. The sample used is the entire population, namely 30 Employees of the Manpower Office. Sources of data in this study are primary data and secondary data. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the results of the study it is concluded that compensation and the physical work environment simultaneously have a significant effect on morale. Partial compensation has a significant effect on work morale. Physical work environment partially has a significant effect on morale.